Association of longitudinal changes in patient-reported health status with return to work in the first 2 years after traumatic injury: a prospective cohort study in the Netherlands - Leonie de Munter; Mariska A C de Jongh; Margot C W Joosen; Koen W W Lansink; Lena Horn; Grigorios Papageorgiou (BMJ Open)
Objectives To determine the prognostic value of time driven changes in health status on return to work (RTW) in the first 2 years after traumatic injury.Design A prospective longitudinal cohort study. All patient-reported outcomes were measured at 1 week, 1, 3, 6, 12 and 24 months after injury.Setting Ten participating hospitals in the Netherlands.Participants Employed adult clinical injury patients admitted to the hospital between August 2015 and November 2016 (N=1245 patients).Main outcome measures Data about (first) RTW were used from the patient-reported questionnaires (1=yes, 0=no). RTW was measured as the first time a patient started working after hospital admission. Time until RTW was calculated in weeks. Health status was measured with the EuroQol Five Dimensions-3 Levels (EQ5D) including a dimension to measure cognition.Results At 24 months, 88.5% (n=1102) of the patients had returned to work. The median time to RTW was 6.6 weeks (IQR: 2–13). Patients’ health status was found to be an independent prognostic factor for RTW: a 0.1-unit increase in EQ5D (scale 0–1) translated into RTW being four times more likely (95% CI 1.60 to 11.94). Patients who had moderate or severe problems (0=no problems, 1=moderate or severe problems) with mobility (HR 0.91, 95% CI 0.84 to 0.98), anxiety/depression (HR 0.86, 95% CI 0.80 to 0.91), usual activities (HR 0.91, 95% CI 0.83 to 0.98), self-care (HR 0.90, 95% CI 0.79 to 0.99) and cognition (HR 0.90, 95% CI 0.85 to 0.94) were significantly less likely to RTW compared with patients with no problems.Conclusion Increased self-reported health status over time is associated with a higher likelihood of RTW, independent of baseline risk factors, such as injury severity or education. Knowledge on patient-reported outcomes can contribute to the development of tailored RTW treatments. Furthermore, patient-reported outcomes could be used as monitoring tool to guide postinjury care in the clinical setting and RTW process.Trial registration number NCT02508675; Results.